Nanodrug Delivery System for Brain Targeting (2024)
Conventional drugs face limitations crossing into the brain allowing for only ideal drug candidates. These candidates should possess properties such as high lipophilicity, moderate molecular weight, charge, etc. This leaves out many other drugs and prevents entry into the brain. The brain protects itself via several barriers that limit drug entry and reduce effectiveness. These barriers include the blood-brain barrier, the blood-cerebrospinal fluid barrier, and the arachnoid barrier. These barriers reduce the efficacy of drugs in the therapy of brain-related diseases. This has necessitated the development of novel strategies such as nanodrug delivery systems, to target drugs to the brain for effective therapies. Nanodrug delivery systems such as liposomes, carbon dots, viral vectors, polymeric micelles, etc., are increasingly being tested in preclinical models and clinical trials in the management of Nanodrug Delivery System for Brain Targeting brain-related diseases. So far, some successes have been recorded for diseases such as Parkinson’s disease, Alzheimer’s disease, Huntington’s Disease, Multiple Sclerosis, etc., While nanodrug systems show promise in future applications, some limitations affect the use in clinical settings. This chapter highlights the current advances in nanodrug delivery systems and their benefits in brain targeting to enhance clinical outcomes